Effects of Topical Honey Dressing in Decubitus Ulcer - Khadanga, S.; Dugar, D.; Karuna, T.; Khetri, R.; Tim, H.; Ghata, S.; Thatoi, P. K. (Asian Journal of Medical Sciences, 2015)
Background: The medicinal properties of honey have been recognized since antiquity. Although used as an adjuvant method for accelerating wound healing from ancient times, honey has been sporadically used in the treatment of wounds. Many researchers have shown that honey exerts antibacterial activity against various organisms, including both Gram-positive and Gram-negative bacteria. This study was done to compare the effectiveness of honey and Povidone iodine in wound healing in Decubitus ulcers. Material & Methods: We conducted a prospective hospital based study of 40 patients with bed sore. Patients were selected considering the inclusion and exclusion criteria. 20 patients (Group A) had honey dressing and another 20 patients (Group B) had Povidone iodine dressing. We compared the wound healing status and bacteriological profile between day 1 and day 10 in both the groups. Result: The pain score decrement was significant in honey dressing group but the reduction in size of the wound was not significant. The bacteriological profile was more or less similar in both the groups. Conclusion: The antibacterial properties of honey, the cost effectiveness, easy availability, reduction in size of wound and more so the significant reduction in pain reveal that honey can be a safe, satisfying, cost effective topical dressing material for decubitus ulcers in general medical and surgical words. DOI: http://dx.doi.org/10.3126/ajms.v6i4.11616 Asian Journal of Medical Sciences Vol.6(4) 2015 99-101